THE IDEOLOGICAL MEANING BEHIND THE SHIFT IN WOMEN'S POSITION IN DOKA NIKISI'E VILLAGE - Marician Sile, Angelius Chrisantho; Wiasti, Ni Made; Suardiana, I Wayan (E-Journal of Cultural Studies, 2023)
Di'i Dhano is a form of marriage system that follows the mother's lineage in Doka Nikisi'e Village. According to this system, a woman inherits all the property of the family in which she lives. However, this marriage system has begun to shift at this time. Even though the matrilineal structure and customary symbolism glorify women, authority, leadership and and access to knowledge about customs, law, politics and technology are dominated by men. This research aims to reveal the causing factors and the hidden ideology of the shift in the position of women in the matrilineal marriage system in Doka Nikisi'e village. This research applies qualitative methods through participant observation, in-depth interviews, and documentation study. Data obtained is analysed critically by feminist theories, namely nature and nurture, liberal feminism, and psychoanalytic theory. The results of this study indicate that the factors causing the shift in women's position include internal and external factors. The hidden ideologies behind the shift in women's positions include patriarchy, masculinity, and power relations. Keywords: Di’i Dhano, ideological, meaning, women’s position